Morvern Callar - Warner, Alan 1964- (Momentum Pictures, 2003)
Morvern Callar is greeted with a startling surprise, her boyfriend has committed suicide. He has left her a cryptic message on his computer and a manuscript for a novel. She changes the author's name to her own and begins a re-birth of self discovery
Original: Großbritannien, Kanada 2002
Bildformat 1.85:1 (16:9 anamorph)
Keywords: Young women / Drama; Suicide / Drama; Plagiarism / Drama; Plagiarism -- Drama; Suicide -- Drama; Young women -- Drama; Film; DVD-Video